To analyze the steps provided in the equation:
-
Start with the original equation: \(3x - 9x + 1 = 2(-3x + 1) - 1\).
-
Combine like terms on the left side: \(-6x + 1 = 2(-3x + 1) - 1\).
-
On the right side, distribute and simplify: \(-6x + 1 = -6x + 2 - 1\) which simplifies to \(-6x + 1 = -6x + 1\).
Now, you see that both sides of the equation are identical, which means:
\(-6x + 1 = -6x + 1\) is always true.
Thus, the true statement is:
There are infinitely many solutions to the equation.
This is because any value of \(x\) will satisfy the equation as it simplifies to a true statement.